FACTORS CORRELATED WITH MEDICAL STUDENTS ANXIETY IN CLINICAL SKILLS EXAMINATION - Anak Agung Gede Pradnya Andika; Yoga Pamungkas Susani; Dian Puspita Sari (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2021)
Background: Test anxiety is one of the medical student’s problems that need attention in medical education. Test anxiety can have negative effect on students such as negative self-evaluation beliefs, low motivation, poor performance, and decreased concentration which can result in increased dropout rates and trigger general anxiety. Test anxiety can affect performance on clinical skill examination and outcomes.Aim: To identify factors correlated with medical students’ anxiety in clinical skills examination.Methods: This was a cross-sectional study involving the second and fourth year medical students in Universitas Mataram. Possible Anxiety Determinant Instrument (PADI) was used to measure factors associated with test anxiety and Performance Test Anxiety (PTA) inventory to measure students’ anxiety in clinical skills examination. Data collection took place after the clinical skill exam. Pearson and Spearman correlation test were used in analyzing the data.Results: Total of 185 students participated in this study (response rate 96,9%). Factors found to be correlated with test anxiety score were internal belief factors (r = -0,686), health and lifestyle factors (r = -0,424), curriculum factors (r= -0,414), social support factors (r = -0,395), learning atmosphere factors (r = -0,312), and examination factors (r = -0,270). Preparedness and experience of examination were not correlated with the test anxiety.Conclusion: Students’ internal belief was found to have the strongest correlation with the test anxiety, while examination factor showed the weakest correlation. These findings can guide medical education institution in developing strategies to reduce students’ anxiety toward the clinical skills examination.